Terrorist threats to food : guidance for establishing and strengthening prevention and response systems. (Food safety issues., 2002)
The malicious contamination of food for terrorist purposes is a real and current threat, and deliberate contamination of food at one location could have global public health implications. This book responds to increasing concern in WHO s Member States that chemical, biological or radionuclear agents might be used deliberately to harm civilian populations and that food might be a vehicle for disseminating such agents. The two major strategies for countering the threat of food sabotage are prevention and response, including preparedness. Chapter 1 introduces the problem and places it in the cont.